Neurotransmitter Related Idiopathic Hypersomnia - Muhammad, Wahyudo Imami; Patricia Wulandari (HM Publisher, 2023)
Idiopathic hypersomnia affects 5% of the adult population, and both men and women are equally susceptible. Excessive sleep, sleep attacks, or wake-time delays are all examples of primary hypersomnia. Hypersomnia can be caused by a mental disorder, an organic condition (such as medications), or it might be idiopathic. This condition is the polar opposite of insomnia. Patients are frequently misdiagnosed as having mental illnesses or being sluggish. Hypersomnia patients require more sleep than the average person. The patient will generally sleep 1-2 times each day, with each nap lasting more than an hour. Despite the fact that they sleep a lot, they are usually weary and sluggish during the day. The causes of hypersomnia can be diverse, including neurological, medical, or psychological disorders. Neurotransmitters can also play a role in regulating a person's sleep patterns and alertness. This review aimed to describe neurotransmitters related to idiopathic hypersomnia.